Colloidal nanoplatelets-based soft matter technology for photonic interconnected networks: low-threshold lasing and polygonal self-coupling microlasers - Duan, Rui (2023)
Soft matter-based microlasers are widely regarded as excellent building blocks for realizing photonic interconnected networks in optoelectronic chips, owing to their flexibility and functional network topology. However, the potential of these devices is hindered by challenges such as poor lasing stability, high lasing threshold, and gaps in knowledge regarding cavity interconnection characteristics. In this study, the first demonstration of a high-quality, low-threshold nanoplatelets (NPLs)-based polymer microfiber laser fabricated using capillary immersion techniques and its photonic interconnected networks are presented. CdSe/CdS@Cd1-xZnxS core/buffer shell@graded-shell NPLs with high optical gain characteristics are adopted as the gain medium. The study achieves a lasing threshold below 14.8 µJ cm−2, a single-mode quality (Q)-factor of ≈5500, and robust lasing stability in the fabricated NPLs-based microfibers. Furthermore, the study pioneers the exploration of polygonal self-coupling microlasers and the optical characteristics of their interconnected fiber network. Based on the signal generation mechanism observed in the photonic networks, an interconnected NPLs-based fiber network structure achieving single-mode lasing emission and laser mode modulation is successfully designed. The work contributes a novel method for realizing microlasers fabricated via soft-matter technologies and provides a key foundation and new insights for unit design and programming for future photonic network systems.